Reinterpreting Local Language Translations: An Analysis of The Mongondow Qur'an and Translation of the Theological Verses of God's Hand and Power - Mokoginta, Djamali (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
The translation of the Qur'an into regional languages such as Mongondow faces both linguistic and theological challenges, particularly when rendering theological verses that contain the concepts of “the Hand” and “the Power of Allah,” which carry the risk of anthropomorphic interpretations. This study aims to identify the translation problems of such verses in the Mongondow Qur'anic translation, with a focus on the accuracy of theological meaning and the relevance to local cultural contexts. Employing Anthony H. Johns' theory of vernacularization, the research analyzes translated texts through a library research method, structured interviews with religious and cultural figures, and descriptive-analytical analysis with theoretical triangulation. The findings indicate that the Mongondow translation tends to adopt a literal approach—for instance, translating yadullāh as lima (hand)—which poses a risk of theological misinterpretation, although in certain verses a metaphorical equivalent such as nonguasa (having power) is used. This inconsistency highlights linguistic, ideological, and epistemological challenges in preserving the Qur'an’s transcendent meanings. The study concludes that Qur'anic translation requires a more nuanced hermeneutic approach involving experts in exegesis and local culture. The academic contribution of this research lies in advancing the discourse on vernacularization in Qur'anic translation studies, offering an analytical framework applicable to other regional languages, and providing practical recommendations to enhance theological accuracy while preserving local cultural identity.